1982
DOI: 10.1111/j.1432-1033.1982.tb05874.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Investigation of the a‐Chymotrypsin‐Catalyzed Hydrolysis of Peptide Substrates

Abstract: Peptide substrates of the general structure Ac-Tyr-Lyl-Lyz-. . -Ly,-NH2 and Ac-Phe-L,,-NHz have been synthesized and subjected to cr-chymotrypsin-catalyzed hydrolysis to collect information on the interactions between the enzyme active site and the amino-acid residues Lyl, Ly2, etc., C-terminal to the susceptible bond of the peptide. For this purpose changes in the dissociation constants of the enzyme-substrate complexes and in the rate constants of acylation have been related to the structural variations of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Further reduction of the number of S subsites diminishes the F value. This finding is in good agreement with the crystal structure of chymotrypsin [lo, 111 and model building analyses [12] which showed that the P3 residues of peptide substrates are involved in two hydrogen bonds with the enzyme. Table 1 shows that the contribution of the P2 and P3 fragments can also be deleted.…”
Section: Which Subsites Have To Be Considered In the Calculation?supporting
confidence: 87%
See 2 more Smart Citations
“…Further reduction of the number of S subsites diminishes the F value. This finding is in good agreement with the crystal structure of chymotrypsin [lo, 111 and model building analyses [12] which showed that the P3 residues of peptide substrates are involved in two hydrogen bonds with the enzyme. Table 1 shows that the contribution of the P2 and P3 fragments can also be deleted.…”
Section: Which Subsites Have To Be Considered In the Calculation?supporting
confidence: 87%
“…Table 1 shows that the contribution of the P2 and P3 fragments can also be deleted. However, we decided to include the P2 fragments in our calculations since the amide groups of these fragments are known to donate a hydrogen bond to the carbonyl oxygen of Phe41 of the enzyme [12]. There are two substrates in the data set with proline residues in the Pi position which, for structural reasons, can not form this hydrogen bond.…”
Section: Which Subsites Have To Be Considered In the Calculation?mentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkable are the outstanding substrate properties of Ac-Phe-Arg-Ser-Val-NH, for both enzymes. There might exist a specific interaction only possible with a C-terminal NH, group of the residue in Pz as proposed in the case of chymotrypsin [55].…”
Section: Substrate Binding Scheme and Interactions With Subsites S3 Amentioning
confidence: 99%
“…Pro are not preferred [27][28][29]. In addition to the three substrates used in this study, we synthesized Mca-Gly-Glu-Pro-Gln-pTyr-Gln-Pro-Lys(DNP)-Arg-NH 2 .…”
Section: Discussionmentioning
confidence: 99%